Persepsi Masyarakat Dusun Gili Trawangan Terhadap Penyebab Terjadinya Bencana Gempa Bumi - Taufiq Ramdani; Muhammad Arwan Rosyadi; Azhari Evendy; Anisa Puspa Rani (Prodi Sosiologi Universitas Mataram, 2020)
An inevitability that natural disasters such as earthquakes will be perceived differently by different individuals within a community, some may perceive earthquakes as a natural occurrence plain and others perceive in transcendental meaning (the relationship of creatures and their Lord), namely the relationship causality between human behavior on the one hand as the cause and the punishment of God through the natural disaster on the other side as a result. This study aims to (1) determine how the perception of Gili Trawangan people to the cause of earthquake that has ever happened, (2) to determine the factors that affect the perception of Gili Trawangan people to the cause of earthquake. This research is down with qualitative paradigm, and case study research as design. Then, the technique of purposive samping and snow ball sampling are used to determine some key informans and support informans. As for in-depth interviews, observation, and documentation are some of the data collection techniques. The research showed that the majority of Gili Trawangan people (71%) perceive that all behaviour and activity of Gili Trawangan community, then the type of tourism business that correlate to party activity, promiscuity, alcohol, as the cause of the earthquake. As for the small percentage (16%) of Gili Trawangan people who are the owner of tourism business perceiving that the earthquake is a natural phenomenon that occurs naturally due to the cyclical annual. As for those who perceive ambiguously are their backgrounds as tourism workers, such as waiters, porters, coachman of horse cart, and others, the amount are 14%. Perception ambiguous question in this research is at one time informants perceive that the cause of the earthquake transcendentally based on religious beliefs but at the same time agree well with the perception that the earthquake is a natural annual cycle. The factors that influence the perception of the above is the level of education, various professions, understanding delivered by preachers and religious leaders, and presentation of information from the mass media.